(untitled) (TAJ: Journal of Teachers Association, 2018)
Chemotherapy services have expanded over recent years. Mothers remain concerned about the safety of their unborn babies while handling hazardous materials. Most chemotherapy drugs are cytotoxic. This means they may be mutagenic, carcinogenic, or teratogenic in nature. How toxic they can be during pregnancy is not absolutely clear. Therefore, handling such drugs may not be 100% safe in pregnancy. Although several chemotherapeutic agents have been proven to be safe for the fetus after the organogenesis period, there is limited information on their use during the first trimester of pregnancy. TAJ 2015; 28(1): 12-15